Computer system under the PADPEEM methodology to estimate aerial carbon in coffee - Márquez de la Cruz, Saira Edith; Cue, Jose Luis Garcia; Fernández Ordoñez, Yolanda M.; Tinoco Rueda, Juan Angel; Del Valle Paniagua, David H.; Sangermán-Jarquín, Dora Maria (Revista Mexicana de Ciencias Agrícolas, 2021)
The research aimed to design a Web-App computer system for data recording in situ and for estimating aerial carbon storage in coffee plots in Huatusco, Veracruz, Mexico. This was raised by the needs of producers to automate calculations of CO2 capture that serve in contributing to climate change mitigation. The software was developed in the Montecillo Campus of the College of Postgraduates from February to October 2020 through the proposal of the PADPEEM methodology and was tested with the data obtained in some coffee crops in Huatusco in January 2020. The results showed the CarbonoCafé system, its architecture, navigation map and interfaces. The CarbonoCafé system will have an impact on the reduction of human, economic and time resources for the calculation of aerial carbon in situ. In addition, it contains databases that can be consulted from any computer or mobile phone.
Keywords: App; climate change mitigation; web system